ANALISIS PRIORITAS PENGEMBANGAN KAWASAN WISATA ALAM GOA DI KABUPATEN TAPIN - AHMAD MUZAKKI RABI; RUDDY SYAFRUDIN (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2019)
This research is aimed (1) to know about what is the most dominant criteria for determining the criteria of development priority cave nature tourism area in tapin regency (2) to know about the most dominant alternative and then the alternative will become focus for development priority of cave nature tourism area in tapin regency.The respondent in this research consist by 7 respondents who recognized expert for the effort of development and determining the priority tourism development area in tapin regency and directly could use as respondents for data processing. The analysis method, using AHP (Analytical Hierarchy Process) method.The result of this research has showed among acces, amenities, and atraction criteria. The most dominant criteria for determined as criteria of priority for supporting the priority development of cave nature tourism area in Tapin Regency is atraction with the preference value 54%, amenities with the preference value 30%, and acces with the preference value 16%. Among two alternatives that is Batu Hapu Cave and Beramban Cave, the highest preference value is Beramban Cave with 69% and the second is Batu Hapu Cave with 31%. It means in the development priority of cave nature tourism area in Tapin Regency more prioritize the development Beramban Cave area. Keyword: Tourism, Tourism Place, Nature Tourism, Batu Hapu Cave, Beramban Cave, AHP Method.